Desarrollo socio productivo de la Cooperativa agrícola 27 de enero del cantón Santa Rosa - Baculima Yauri, Lusi Eduardo (2013)
The hypothetical approach was confirmed, so a proposal has been implemented whose program of motivation and productive training for the members of the cooperative January 27 in the city of Santa Rosa which consists in guiding the farmer towards a better organization and application .